2022
DOI: 10.7759/cureus.32907
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Chlorhexidine and Herbal Mouthwash Against the Adherence of Microorganism to Sutures After Periodontal Surgery: A Clinical Microbiological Study

Abstract: Introduction: Chemical plaque control agents assist to eliminate plaque microorganisms. Therefore, the purpose of this research was to compare the effectiveness of a herbal mouthwash (HiOra TM ) and a mouthwash containing 0.2% chlorhexidine in preventing bacteria from adhering to sutures in participants who had had periodontal flap surgery.Material and methods: 75 patients with chronic periodontitis were included in the study and divided into three groups. Plain water, herbal, and chlorhexidine mouthwashes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Chlorhexidine does not interact with microbial enzymes or receptors so it does not cause resistance in the organism. 27 Chlorhexidine belongs to the biguanide group whose mechanism of action damages the microbial cell membrane by coagulating cytoplasmic proteins. 28 Antimicrobials include vegetative bacteria, fungi and viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorhexidine does not interact with microbial enzymes or receptors so it does not cause resistance in the organism. 27 Chlorhexidine belongs to the biguanide group whose mechanism of action damages the microbial cell membrane by coagulating cytoplasmic proteins. 28 Antimicrobials include vegetative bacteria, fungi and viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Citronella oil dilution was carried out by adding n-hexane. Chlorhexidine was acted as the positive control because it was reported that Chlorhexidine was an antiseptic that could go averse to both types of bacteria, viruses, and facultative aerobes and anaerobes (14). The growth control was used as the negative control.…”
Section: Methods Preparation Of Citronella Oilmentioning
confidence: 99%
“…20 Further, the efficacy of these herbal mouthwashes on the management of various oral pathologies is comparable to commonly used antibacterial synthetic chemicals and alcohol-based mouthwashes. 21,22 In a recent study conducted by Tidke et al (2022), aloe vera, a potent antimicrobial agent, was shown to be effective in removing plaque and ameliorated symptoms of dental caries, including tooth hypersensitivity, toxicity, and tooth staining. 22 Notably, aloe vera was found to be equally effective as chlorhexidine (CHX) mouthwash, a nonherbal antiseptic medication that is considered the gold standard in the prevention of dental plaque and treatment of gingivitis and periodontitis.…”
Section: Herbal Mouthwashesmentioning
confidence: 99%